Modern weapons and military equipment for issue 3-2015 - Jevtić, Miloš M. (Vojnotehnički glasnik / Military Technical Courier, 2015)
Optimal features for concealed carry weaponsThe specificity of jobs and tasks that require concealed carrying of weapons by officials require specific criteria when choosing personal weapons specialist.